Inflammation and breast cancer. (July 2013) - Constantinou, Chloe; Fentiman, Ian S
SUMMARY The relationship between breast cancer (BC) and inflammation remains unclear. Some risk factors, such as age, obesity and postmenopausal status, are also associated with increased levels of circulating proinflammatory cytokines and systemic inflammation. The role of T lymphocytes during BC development has been the subject of great debate, with improved survival reported when CD8 + and CD3 + T-lymphocytic infiltrates are present. Studies of B-lymphocytic infiltrates and prognosis have yielded conflicting results, but the extent of infiltration of tumor-associated macrophages is associated with reduced relapse-free and overall survival. There is consistent evidence that increased levels of proinflammatory factors, such as IL-6, IL-1β and TNF-α, and inflammatory chemokines, such as CCL2 and CCL5, are associated with increased risk of BC and poorer prognosis. However, it is not known whether this actually plays a role in tumor development. Substantially more work is needed to achieve a basis for effective anticancer therapy.